Biocontrol Potential of Streptomyces sp. from the Avicennia marina Rhizosphere against Sclerotium rolfsii in Bird’s Eye Chili (Capsicum frutescens L.) - Yerni Andryani; Arika Purnawati; Tri Mujoko (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to evaluate the potential of Streptomyces sp. isolated from the rhizosphere of the mangrove Avicennia marina as a biological control agent against Sclerotium rolfsii, the causal agent of basal stem rot in bird’s eye chili (Capsicum frutescens L.). The study was conducted using a non-factorial completely randomized design consisting of a control treatment and root-soaking treatments in a Streptomyces sp. suspension for different durations: 15, 30, and 45 minutes. Observational data were analyzed using ANOVA at the 5% significance level with IBM SPSS Statistics version 27. The results showed that Streptomyces sp. inhibited the growth of S. rolfsii on artificial medium by up to 52.33%, indicating strong antagonistic activity. The in vivo assay further demonstrated that the 45-minute root-soaking treatment (SW3) delayed disease incubation until the final day of observation, prevented the development of disease symptoms throughout the observation period, and enhanced vegetative growth in bird’s eye chili plants. These findings suggest that Streptomyces sp. from the rhizosphere of A. marina has promising potential as a biological control agent for managing basal stem rot caused by S. rolfsii in bird’s eye chili.